2017
DOI: 10.1021/acs.jnatprod.6b00697
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpenoid Indole Alkaloids from Kopsia officinalis and the Immunosuppressive Activity of Rhazinilam

Abstract: Six new monoterpenoid indole alkaloids, kopsinidines C-E (1-3), 11,12-methylenedioxychanofruticosinic acid (4), 12-methoxychanofruticosinic acid (5), and N(4)-methylkopsininate (7), as well as chanofruticosinic acid (6, as a natural product) and 23 known alkaloids, were obtained from the twigs and leaves of Kopsia officinalis. Their structures were characterized by physical data analysis. All isolated compounds were evaluated for their immunosuppressive activity on human T cell proliferation. Rhazinilam (29) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 37 publications
(62 reference statements)
0
56
0
Order By: Relevance
“…All isolated compounds were evaluated for the inhibitory activity against human T cell proliferation according to reported protocols [17]. Compounds 1 and 6 showed immunosuppressive activity on human T cell proliferation, with IC 50 values of 5.9 µM and 5.0 µM, respectively.…”
Section: Immunosuppressive Activity Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…All isolated compounds were evaluated for the inhibitory activity against human T cell proliferation according to reported protocols [17]. Compounds 1 and 6 showed immunosuppressive activity on human T cell proliferation, with IC 50 values of 5.9 µM and 5.0 µM, respectively.…”
Section: Immunosuppressive Activity Assaymentioning
confidence: 99%
“…The air-dried and powdered whole plants of R. yunnanensis (8.5 kg) were extracted as described before to yield CHCl 3 and n-BuOH extractions [17]. The CHCl 3 extraction (79.6 g) was subjected to silica gel CC eluted with a step gradient CHCl 3 -MeOH (50:1 to 0:1) system.…”
Section: Extraction Isolation and Purification Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjecting 24 to a similar reaction sequence as described above gave 26 and demethoxycarbonylkopsin sequentially, whose structures were unambiguously determined by X‐ray crystallographic analysis . Further reduction of the ketone with LiAlH 4 produced kopsinidine C and its epimer. Notably, our 1 H and 13 C NMR data of demethoxycarbonylkopsin were identical to those reported by the Qin group, but not in agreement with those taken from natural demethoxycarbonylkopsin, as mentioned by Qin and co‐workers.…”
Section: Figurementioning
confidence: 99%
“…Further reduction of the ketone with LiAlH 4 produced kopsinidine C and its epimer. Notably, our 1 H and 13 C NMR data of demethoxycarbonylkopsin were identical to those reported by the Qin group, but not in agreement with those taken from natural demethoxycarbonylkopsin, as mentioned by Qin and co‐workers. We found that this problem could be solved by adding a trace amount of TFA when collecting NMR spectroscopic data.…”
Section: Figurementioning
confidence: 99%